Role of Interferons in the Function of the Immune System - Alizada, Mohammad Naiem (Journal of Natural Sciences – Kabul University, 2020)
Interferons are a family of endocrine and paracrine cytokines secreted by host cells in response to pathogenic agents, particularly viruses and bacteria. Interferons are small proteins that belong to the group of cytokines and act as the first line of defense against pathogens. There are three types of interferons: Type I, Type II, and Type III. They are usually produced rapidly during viral infections, highlighting their important role in controlling viral infections. Interferons also affect the immune system and inhibit tumor growth. This paper aims to review the various aspects of interferon function in the defense system, focusing on their structure, function, and mechanism of action during viral infections.